Pengaruh Kepemilikan Asing, Komisaris Independen dan Leverage Terhadap Kualitas Audit di Indonesia (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Hidayati, Siti Nur; , Dr. Noer Sasongko SE.,Ak.,M.Si (2017)
This study aimed to describe empirically the effect of foreign ownership, independent commisioner and leverage against the quality audit in Indonesia on manufacturing companies listed in Indonesia Stock Exchange in 2012-2015. The population in this study using manufacturing companies listed in Indonesia Stock Exchange in 2012-2015. Sampling was done by using purposive sampling method and obtained a sample of 28 companies. Secondary data colletion methods based on data published Indonesia Stock Exchange during the period 2012-2015. Data were analyzed using logistic regression. The result showed that foreign ownership and independent directors have an influence on the selection of auditors in Indonesia. While leverage does not effect the auditor selection in Indonesia.